Chronic obstructive pulmonary disease from the perspective of medicine based on evidence. - Gerardo Rivero González; Rolando Delgado Figueredo; Iris González Morales (Medisur)
Acute exacerbations of chronic obstructive pulmonary diseases which require hospitalization are associated to an increment of the mortality rate which in the case of patients who need treatment in an ICU goes up from 4 % to 11 or 12 % of the patients. This article made on bibliographical revision shows the main therapeutics pharmacological and non pharmacological options used in case of an acute decompensation of this disease based on the main available evidences. Main medications that can diminish the frequency of the readmission and mortality are described.